Improving EDLC Device Performance Constructed from Plasticized Magnesium Ion Conducting Chitosan Based Polymer Electrolytes via Metal Complex Dispersion - Shujahadeen B. Aziz; Elham M. A. Dannoun; M. H. Hamsan; Rebar T. Abdulwahid; Kuldeep Mishra; Muaffaq M. Nofal; M. F. Z. Kadir (Membranes, 2021)
The current work shows the preparation of plasticized chitosan-magnesium acetate Mg(CH3COO)2-based polymer electrolyte dispersed with nickel (Ni) metal complexes via solution casting. Investigations of electrical and electrochemical properties of the prepared polymer composite electrolyte were carried out. The structural and optical properties of the samples were studied using X-ray diffraction (XRD) and UV-Vis spectroscopy techniques. The structural and optical outcomes revealed a clear enhancement in both absorbance and amorphous nature of the samples upon the addition of Ni metal complexes. Through the simulation of impedance data, various ion transport parameters were calculated. The electrochemical performance of the sample was examined by means of transference number measurement (TNM), linear sweep voltammetry (LSV) and cyclic voltammetry (CV) measurements. The TNM analysis confirmed the dominance of ions as the main charge carrier in the electrolyte with tion of (0.96) compared to only (0.04) for tel. The present electrolyte was stable in the range of 0 V to 2.4 V, which was obtained from linear sweep voltammetry (LSV). A result from CV proved that the electrical double-layer capacitor (EDLC) has a capacitive behavior as no redox peaks could be observed. The presence of Ni improved the charge–discharge cycle of the EDLC due to its amorphous behavior. The average performances of the EDLC were recorded as 41.7 F/g, 95%, 5.86 Wh/kg and 628 W/kg for specific capacitance, coulombic efficiency, energy and power densities, respectively. The fabricated EDLC device was found to be stable up to 1000 cycles.